THE IMPLEMENTATION OF TOUR PACKAGE PROMOTIONS ON PT. REZKI JASTY TOUR & TRAVEL PEKANBARU - Ramadhan, Anugerah; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Promotion is an important part of marketing, with the promotion, customers or prospective buyers can find out information about a company's products. The tool for carrying out promotional activities is called the promotional mix. This study aims to determine how the implementation of tour package promotion at PT. Rezki Jasty Tour & travel Pekanbaru. This study used a qualitative method with a descriptive approach to describe the real situation by collecting field information data. The key informants in this study were 1 main director and 2 employees of PT. Rezki jasty Tour & Travel Pekanbaru, while the data collection techniques in this study used interviews, observation, and documentation based on the results of the research which showed that the promotion mix conducted by PT. Rezki Jasty Tour & Travel Pekanbaru is advertising, sales promotion, public relations, face to face sales, direct marketing using direct contact as well as telephone and email.Â Key words :Promotion mix, Tour package, Travel Â